Organized Materiality: A study of material culture and space of the late medieval Swedish guilds. Issue 1 (1st January 2017) - Nordin, Jonas M.
Abstract : In the late medieval period the religious guilds along with trade guilds grew in importance, as did the role of material culture related to the guilds. This history has seen little examination from a Fenno-Scandinavian and particularly a Swedish vantage point. In order to analyse the role of material culture in the formation of this way of organizing people, the article investigates the existence of late medieval guildhalls, especially rural ones, and discusses remains of other material culture that can be connected to the guilds. The halls, drinking vessels and other material things were activated in the growth of a new more substantial way of organizing society outside the boundaries of feudal society and family control. It is argued that material culture had a significant role in the recurrent activities of the guilds of the Middle Ages and in the shaping of new ways of organizing people.